A Flat World, a Level Playing Field, a Small World After All, or None of the Above? A Review of Thomas L. Friedman's The World is Flat - Leamer, Edward E (Journal of Economic Literature, 2007)
Geography, flat or not, creates special relationships between buyers and sellers who reside in the same neighborhoods, but Friedman turns this metaphor inside-out by using The World is Flat to warn us of the perils of a relationship-free world in which every economic transaction is contested globally. In his “flat” world, your wages are set in Shanghai. In fact, most of the footloose relationship-free jobs in apparel and footwear and consumer electronics departed the United States several decades ago, and few U.S. workers today feel the force of Chinese and Indian competition, notwithstanding the alarming anecdotes about the outsourcing of intellectual services. Of course, standardization, mechanization, and computerization all work to increase the number of footloose tasks, but innovation and education work in the opposite direction, creating relationship-based activities—like the writing of this review. It may only be personal conceit, but I imagine there is a reason why the Journal of Economic Literature asked me to do this review.